Ischemic Strokes Due to Large-Vessel Occlusions Contribute Disproportionately to Stroke-Related Dependence and Death: A Review - Malhotra, Konark; Gornbein, Jeffrey; Saver, Jeffrey L. (Frontiers in Neurology, 2017)
Background: Since large vessel occlusion (LVO) related acute ischemic strokes (AIS) are associated with more severe deficits, we hypothesize that the endovascular thrombectomy (ET) may disproportionately benefit stroke-related dependence and death. Methods: To delineate LVO-AIS impact, systematic search identified studies measuring dependence or death (modified Rankin Scale 3-6) or mortality following ischemic stroke among consecutive patients presenting with both LVO and non-LVO events within 24 hours of symptom onset. Results: Among 197 articles reviewed, 2 met inclusion criteria, collectively enrolling 1467 patients. Rates of dependence or death (mRS 3-6) within 3-6 months were higher after LVO than non-LVO ischemic stroke, 64% vs. 24%, odds ratio (OR) 4.46 (CI: 3.53-5.63, p<0.0001). Mortality within 3-6 months was higher after LVO than non-LVO ischemic stroke, 26.2% vs. 1.3%, OR 4.09 (CI: 2.5-6.68), p<0.0001. Consequently, while LVO ischemic events accounted for 38.7% (CI: 21.8-55.7%) of all acutely presenting ischemic strokes, they accounted for 61.6% (CI: 41.8-81.3%) of poststroke dependence or death and 95.6% (CI: 89.0-98.8%) of poststroke mortality. Using literature-based projections of LVO cerebral ischemia patients treatable within 8h of onset, ET can be used in 21.4% of acutely presenting patients with ischemic stroke, and these events account for 34% of poststroke dependence and death and 52.8% of poststroke mortality. Conclusion: LVOs cause a little more than one-third of acutely presenting AIS, but are responsible for three-fifths of dependency and more than nine-tenths of mortality after AIS. At the population level, endovascular thrombectomy has a disproportionate benefit in reducing severe stroke outcomes.